Some remarks on the argument appealing to nature against synthetic biology - Lei, Ruipeng; Peng, Yifan; He, Yutian; Li, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
This paper will focus on analyzing the argument with appealing to nature against synthetic biology and provide a counter-argument against it through demonstrating the ambiguity of the concept of nature, denying the existence of a morally significant line between natural and non/unnatural, and disproving the allegations against synthetic biology raised by the argument appealing to nature. The paper consists of two parts following a brief introduction. The first part will describe the argument appealing to nature against synthetic biology, and identify the deficiencies of the argument per se, e.g., the ambiguity of the concept ‘nature’; and the problems in the morally significant line between the natural and the non/unnatural. The second part will discuss the allegations to synthetic biology stemming from this argument, e.g., committing metaphysical and ethical mistakes, and doing possible harms to the environment.